New methodological perspectives in Islamic studies - Hughes, Aaron W.; Aghdassi, Abbas (Supplements to method & theory in the study of religion, 2023)
"This volume draws attention to and moves beyond the traditional methodological frames that have governed knowledge production in the academic study of Islam. Departing from Orientalist and largely textual studies, the chapters collected herein revolve around three main themes: gender, the political, and what has come to be known as "lived Islam." The first involves ascertaining how to read gender and gender issues into traditional sources. The second encourages an attunement to the often delicate intersection between the spheres of religion and politics. The final provides a corrective to our traditional over-emphasis on the interpretation of texts and a preoccupation with studying (mainly male) elites. Taken as a whole, this volume encourages a multi-methodological approach to the study of Islam. Contributors include Abbas Aghdassi, Aaron W. Hughes, Eva Kepplinger, Taira Amin, Betül Avcı, Ali Abedi Renani and Seyyed Ebrahim Sarparast Sadat, Meral Durmuş and Bahattin Akşit, Walid Ghali, Isabella Crespi and Martina Crescenti, Brian Arly Jacobsen, Pernille Friis Jensen, Kirstine Sinclair, and Niels Valdemar Vinding, Magdalena Pycińska, Zahraa McDonald, Emin Poljarevic, Abdessamad Belhaj"--